Subperiosteal and Citelli abscesses as rare complications of chronic suppurative otitis media - Handoko, Edi; Sunanto, Selina Hans (PERHATI-KL, 2025)
Background: Citelli abscess, is a rare extracranial complication of malignant chronic suppurative otitis media (CSOM), constitutes of a subperiosteal abscess extending from the mastoid medial aspect into the digastric fossa. Its infrequency often leads to underreporting, and delayed recognition can have severe consequences. Purpose: To present a case of malignant CSOM complicated by subperiosteal and Citelli abscesses. Case report: A 31-year-old male was diagnosed with left ear CSOM, with subsequent extracranial complications. Computed Tomography (CT) of the head and neck revealed cholesteatoma-associated ossicular damage, subperiosteal abscess, and Citelli abscess, extending intracranially to the extra-axial zone of the left temporal region. The patient underwent incision and drainage prior to receiving CT scan results, followed by a radical mastoidectomy and broad-spectrum antibiotic treatment. Clinical question: “In patients with CSOM, how does the prevalence of extracranial complications compared to intracranial complications in terms of frequency and associated clinical outcomes?” Method: A systematic search of PubMed, ProQuest, EBSCOhost, and Medline identified studies on extracranial and intracranial complications of CSOM published between 2019 and 2024. Result: Out of identified 84 articles, 6 met the inclusion criteria. Extracranial complications were more common, though regional variations emphasized the need for vigilance regarding intracranial complications due its severity. Conclusion: Subperiosteal abscesses, including Citelli abscesses, are rare but serious extracranial complications of CSOM. Prompt surgical intervention and targeted antibiotic therapy are crucial for favorable outcomes.